1982
DOI: 10.1126/science.7123235
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Parchman: Double Crossover Within a Single Human Gene

Abstract: Structural analysis of a new variant hemoglobin revealed tryptic peptides with the amino acid composition of normal delta-globin, except for two internal peptides, which had the compositions of normal beta-globin. The most likely explanation for these findings is that a double, nonhomologous crossover between the delta-and beta-globin genes had occurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…For example, we detected recurrent conversions between the human β- and δ-globin genes. Evidence for a similar but presumably much more recent event has been reported in a patient exhibiting mild microcytosis, whose δ-globin gene contained part of the amino acid sequence of the β-globin gene [37]. The authors of that report hypothesized that this could have been due to a new gene conversion.…”
Section: Resultsmentioning
confidence: 58%
“…For example, we detected recurrent conversions between the human β- and δ-globin genes. Evidence for a similar but presumably much more recent event has been reported in a patient exhibiting mild microcytosis, whose δ-globin gene contained part of the amino acid sequence of the β-globin gene [37]. The authors of that report hypothesized that this could have been due to a new gene conversion.…”
Section: Resultsmentioning
confidence: 58%
“…One consequence of such a double cross-over would be the production of a chromosome lacking a but expressing an a-6-a gene, an event consistent with the inheritance of the Dantu antigen in cells of this type (Contreras et al, 1984). An analogous hybrid (haemoglobin Parchman) has recently been described between 6and ,?-haemo-globins (Adams et al, 1982). One prediction of this hypothesis would be the existence of Dantu-positive (a-6-a) molecules carrying an M antigen that would be Pronase-resistant on intact erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Hb Parchman (Adams et al 1982) seems to be another example of δ-globin gene conversion by the β-gene. Adams et al (1982) have shown that the mutated δ-globin chain has two variant amino-acids (δ22 Ala→Glu and δ50 Ser→Thr), which are the same as the β-globin "wild-type" chain. Although these data have been interpreted as a double crossover event, a con-120 (Beldjord et al 1992), the 3' boundary of the conversion, in the case of Hb F-Charlotte, might be located at position +1507, reducing the length of the converted fragment to 333 bp d The Gγ-Atlanta HPFH is a characteristic example of a "patchy" conversion event e The origin of the Cretan type of the non-deletional HPFH mutation by two different gene conversion events is unique in the human globin gene region Fig.…”
Section: Figmentioning
confidence: 99%